People of the book : a novel - Brooks, Geraldine (New York : Viking, 2008)
In 1996, Hanna Heath, a young Australian book conservator is called to analyze the famed Sarajevo Haggadah, a priceless six-hundred-year-old Jewish prayer book that has been salvaged from a destroyed Bosnian library. When Hanna discovers a series of artifacts in the centuries' old, she unwittingly exposes an international cover up
Map on endpapers
Keywords: Judaism -- Prayers and devotions -- Fiction; Books -- Conservation and restoration -- Fiction